Comparative Single-Cell Transcriptomics Reveals Novel Genes Involved in Bivalve Embryonic Shell Formation and Questions Ontogenetic Homology of Molluscan Shell Types - Salamanca-Díaz, David A.; Ritschard, Elena A.; Schmidbaur, Hannah; Wanninger, Andreas (Frontiers in Cell and Developmental Biology, 2022)
Mollusks are known for their highly diverse repertoire of body plans that often includes external armor in form of mineralized hardparts. Representatives of the Conchifera, one of the two major lineages that comprises taxa which originated from a uni-shelled ancestor (Monoplacophora, Gastropoda, Cephalopoda, Scaphopoda, Bivalvia), are particularly relevant regarding the evolution of mollusk shells. Previous studies have found that the shell matrix of the adult shell (teleoconch) is rapidly evolving and that the gene set involved in shell formation is highly taxon-specific. However, detailed annotation of genes expressed in tissues involved in the formation of the embryonic shell (protoconch I) or the larval shell (protoconch II) are currently lacking. Here, we analyzed the genetic toolbox involved in embryonic and larval shell formation in the quagga mussel Dreissena rostriformis using single cell RNA sequencing. We found significant differences in genes expressed during embryonic and larval shell secretion, calling into question ontogenetic homology of these transitory bivalve shell types. Further ortholog comparisons throughout Metazoa indicates that a common genetic biomineralization toolbox, that was secondarily co-opted into molluscan shell formation, was already present in the last common metazoan ancestor. Genes included are engrailed, carbonic anhydrase, and tyrosinase homologs. However, we found that 25% of the genes expressed in the embryonic shell field of D. rostriformis lack an ortholog match with any other metazoan. This indicates that not only adult but also embryonic mollusk shells may be fast-evolving structures. We raise the question as to what degree, and on which taxonomic level, the gene complement involved in conchiferan protoconch formation may be lineage-specific or conserved across taxa.